Comparison of Oral Misoprostol with Intramuscular Oxytocin in the Active Management of Third Stage of Labour - Kaudel, S; Rana, A; Ojha, N (Nepal Journal of Obstetrics and Gynaecology, 2015)
Aims: This study aimed at comparing the efficacy of oral misoprostol 600 mcg with intramuscular oxytocin 10 IU in the active management of third stage of labour. Methods: This prospective comparative study was performed in Tribhuvan University Teaching Hospital to compare the efficacy of oral misoprostol with intramuscular oxytocin in the third stage of labour for the prevention of postpartum hemorrhage. One hundred and twenty women without risk of PPH were randomly allocated to receive either 600 mcg misoprostol orally (Group A) or 10 unit of oxytocin intramuscularly (Group B) within 1 minute of delivery. The efficacy and the safety of these two drugs were analyzed on the basis of percentages fall in hemoglobin (Hb) and hematocrit (Hct) level from before delivery to 8 completed hours after delivery, need for additional uterotonic agents, need for exploration and uterine evacuation, need for blood transfusion, duration of third stage of labour and the numbers of retained placenta and need for MRP. Results: Oral misoprostol was observed to be equally effective as intramuscular oxytocin in prevention of post-partum hemorrhage (PPH). There was no statistical difference in the duration of third stage of labour, need for additional uterotonics, need for uterine exploration/evacuation and need for blood transfusion in the two groups. Conclusions: Routine use of oral misoprostol 600 mcg appears to be as effective as 10 IU intramuscular oxytocin in minimizing blood loss during the third stage of labour.